Answer:
7x + 6 = 6x - 3
Step-by-step explanation:
2(x+3) + 5x = 3(2x-1)
Distribute
2x + 6 + 5x = 6x - 3
Combine like terms
7x + 6 = 6x - 3
hope this helps
Answer:
4√10xy/32y is the answer. (I think)
Circle<span> is the locus of points equidistant from a given point, the center of the </span>circle<span>. The common distance from the center of the </span>circle<span> to its points is called radius. Thus a </span>circle<span> is completely </span>defined<span> by its center (O) and radius (R): C(O, R) = O(R) = {x: dist(O, x) = R}.
Easier explanation: </span><span>A </span>circle<span> is a plane figure contained by one line such that all the straight lines falling upon it from one point among those lying within the figure are equal to one another.</span>
Answer:
Option D
Step-by-step explanation:
Because, there is equals symbol in the equation.